A novel tape-free sample preparation method for human osteochondral cryosections for high throughput hyperspectral imaging. - Fan, Xiwei; Donose, Bogdan; Jones, Michael W. M.; Howard, Daryl; Torniainen, Jari; Bertling, Karl; Guo, Xiao; Kewish, Cameron M.; Lee, Kah Meng; Sun, Antonia Rujia; Rakic, Aleksandar; Crawford, Ross; et al. (Histochemistry & Cell Biology, 2025)
Understanding the osteochondral junction, where non-mineralised cartilage and mineralised bone converge, is crucial for joint health. Current sample preparation techniques are insufficient for detailed spatial hyperspectral imaging analysis. Using the enhanced Kawamoto method, we used the super cryo embedding medium’s temperature-dependent properties to transfer high-quality tissue samples onto slides for spatial imaging analysis. We transferred osteochondral samples using a tape-free system and successfully tested them in hematoxylin and eosin (HE), Safranin-O, nanomechanical assessments and nano-Fourier transform infrared (FTIR) mapping. This protocol elucidates the structural and elemental gradients, mechanical characteristics and distinctive biochemical layering, making it a useful tool for analysing biochemical properties’ co-distribution in healthy and diseased situations.